With Geely, Proton can achieve economies of scale - New Sabah Times English, (KK) (New Sabah Times, 2017)
KUALA LUMPUR: The economies of scale factor which has eluded national carmaker Proton Holdings Bhd for a long time, can be achieved via its newlysigned strategic partnership agreement with China's Geely, a research institute director said Sunday.